Mechanism of constipation and response to diet: novel insights from manometry and magnetic resonance imaging - Wilkinson-Smith, Victoria (2020)
Constipation is a common condition in which an individual suffers with hard stools which are infrequent and difficult to pass. It has an estimated prevalence of 15-20% however the pathophysiology of symptoms remains poorly understood and treatment is often unsatisfactory for patients. In approximately 60% of patients their constipation is associated with abdominal pain, whilst in the remaining this appears in absence of pain.